2019
DOI: 10.1111/jce.14114
|View full text |Cite
|
Sign up to set email alerts
|

A prolonged QTc‐interval at the emergency department: Should we always be prepared for the worst?

Abstract: Introduction QTc‐interval prolongation is associated with ventricular arrhythmias and mortality in a general population. Bazett's correction formula (QTcB) is routinely used despite its overcorrection at high heart rates. Recently, we proposed a patient‐specific QT correcting algorithm (QTcA) resulting in improved rate correction and predictive value in a general population. We hypothesize risk stratification at the Emergency Department (ED) could be improved using QTcA. Methods and Results A retrospective cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Previous studies estimate that the prevalence of LQTS in the ED is 30%-40%. [17][18][19][20] Our results show that this syndrome is particularly common in this setting, even when accounting only for patients with a severely prolonged QTc. Similar to other studies, we detected that these were mainly older patients (73.49±14.79 years).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Previous studies estimate that the prevalence of LQTS in the ED is 30%-40%. [17][18][19][20] Our results show that this syndrome is particularly common in this setting, even when accounting only for patients with a severely prolonged QTc. Similar to other studies, we detected that these were mainly older patients (73.49±14.79 years).…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies reported a prevalence between 28.5%-35% in the ED for QT prolongation, both acquired and hereditary. [17][18][19][20] Also, approximately 25% of the patients admitted to cardiac intensive care units (ICUs) had prolonged QTc intervals at admission [3] and 20%-24% had severely prolonged QTc intervals when admitted to any ICU. [21,22] The prevalence of QTc interval greater than 500 ms in other hospital wards was 0.7%-0.9%.…”
Section: Introductionmentioning
confidence: 99%
“…14,16 In the acute setting at an emergency department, the use of appropriate QT correction formulas has shown to reduce the number of patients considered to have a prolonged QTc by 65%. 17 In patients with liver disease, the Fridericia formula has recently been shown to be superior over other formulas and its use is therefore recommended in patients with cirrhosis. [18][19][20] Identifying significant QTc prolongation starts with defining normal values (Table 1).…”
Section: The Corrected Qt (Qt C ) Intervalmentioning
confidence: 99%
“… 11 , 14 The short-term predictive value for a prolonged QTc at the emergency department to predict in-hospital mortality was limited, whereas a severely prolonged QTc >500 ms was associated with in-hospital cardiovascular events. 17 …”
Section: Long Qt Syndromementioning
confidence: 99%
See 1 more Smart Citation